Relation between the Winning of Fidesz Party with the Number of Incoming Asylum Seekers in Hungary - Prakoso, Septyanto Galan; Murtyantoro, Andriansyah Perdana; Cahyani, Meisya Putri Intan; Putra, Ferdian Ahya Al (Jurnal Review Politik, 2023)
The migrant crisis that occurred back in 2015 has sparked various political turbulence in European countries. One of the highest “first-time application” countries is Hungary. But as the number of asylum seekers grows, the Hungarian government considered itself overburdened and thus decided to take action to limit the inflow number of asylum-seekers. This situation gives Hungarian Prime Minister Viktor Orban and his Fidesz Party a way to keep campaigning for anti-immigrant policy which he believes will gain massive support. This journal uses a mixed-research method to find out the relation between the winning Fidesz Party with the number of incoming asylum seekers in Hungary. The analysis will be based on a regression process to determine the correlation between the votes that caused the Fidesz Party to win the last five general elections of Hungary with the quantity of asylum seekers in Hungary during the election year and supported by data observed from literature research.